PERSEPSI ANAK USIA 12 TAHUN TERHADAP FILM ANIMASI NUSSA DAN RARA EPISODE LIBUR JANGAN LALAI DI DESA KLECOREGONANG KECAMATAN WINONG KABUPATEN PATI - Amiliya Nurul Jannah; Erik Aditia Ismaya; Deka Setiawan (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to analyze the perception of children aged 12 years towards the animated film Nussa and Rara in the holiday episode, don't be negligent. Film is an interesting medium that can deliver the message contained in the film. The types of films that children like are animated films. One type of animated film that has a positive moral message is the animation of Nussa and Rara. This research is a qualitative descriptive research conducted in Klecoregonang Village, Winong District, Pati Regency. The informants in this study were children aged 12 years. Methods of collecting data through observation, interviews, and documentation. The data analysis used includes data reduction, data presentation, verification or conclusion. The researcher uses data analysis of the perception stages from Walgito. There are three perceptual indicators, namely acceptance of stimuli, understanding, and assessment. The results showed that in receiving the object the child could give a perception of the characters in the film. At the stage of understanding the child is able to describe the characteristics contained in the character, the content of the film and the character. In the assessment, the child gave a positive assessment of the animated film Nussa and Rara.